Sexually transmitted infections associated with depressive syndrome in women aged 15 to 49 years in Peru, 2022 to 2023 - Espinal Asenjo , Olga Liz (2025)
Introduction: Sexually transmitted infections (STIs) and depressive syndrome are public health issues that affect the quality of life of women of reproductive age. Objective: To determine the association between STIs and depressive syndrome in Peruvian women aged 15 to 49 years, based on the 2022–2023 Demographic and Family Health Survey (ENDES). Materials and Methods: A cross-sectional, analytical, and retrospective study using secondary data from ENDES. STIs were identified through self-report, and depressive syndrome was assessed using the Patient Health Questionnaire-9. Sociodemographic variables included age, marital status, educational level, area of residence, and wealth index. Crude and adjusted prevalence ratios (PR) were estimated using Poisson regression models with robust variance, considering p<0.05 as statistically significant. Results. Seeking treatment for STIs was associated with higher prevalence of depressive symptoms (adjusted PR=1.15; 95 %CI: 1.04–1.28; p=0.010), while STI diagnosis itself was not significantly associated. Higher prevalence was also observed among women with secondary education (PR=0.86; 95%CI: 0.76–0.99; p=0.029) and higher education (PR=0.85; 95 %CI: 0.72–0.99; p=0.040), those in the middle wealth index (PR=1.19; 95 %CI: 1.00–1.42; p=0.050), and women reporting two to three sexual partners (PR=1.15; 95 %CI: 1.04–1.28; p=0.010). Conclusion: Although no significant association was found between STI diagnosis and depressive syndrome, seeking treatment was linked to higher prevalence. These findings highlight the need for strategies that integrate mental health into STI care, particularly for socially vulnerable women.